Phased human-nature interactions for the past 10 000 years in the Hexi Corridor, China - Yu Li; Mingjun Gao; Zhansen Zhang; Junjie Duan; Yaxin Xue (Environmental Research Letters, 2023)
Located in the eastern section of the ancient Silk Road, the Hexi Corridor is a crucial area where eastern and western civilizations met. Previous studies mainly explore human-nature interactions at a particular period, and there is a lack of phased human-nature interaction studies at long time scales. Here we present the relationships and patterns of interaction between humans and nature in the region over the past 10 000 years and distinguish the stages and mechanisms of interaction, which can be divided into three periods in the region. 10 000–4000 a BP is a period of weak interaction when human activities and natural processes are primarily non-interactive. The evolution of culture advances in its way rather than by environmental changes, and those early cultures do not strongly impact the natural environment. During 4000–2000 a BP, climate change becomes the dominant factor in human adaptation, mitigation, and migration in the region, and extreme short-term changes often impact the social system, intensifying the impact of nature on humans. Therefore, it is a strong interaction period (nature domination). From 2000 to 0 a BP, humans dominate environmental change manifested by surface processes, lake evolution, and regional water resource changes. At the same time, environmental change can backfire on humans, causing a series of social crises. Overall, it is a strong interaction period (human domination). We propose a Hexi model, a weak interaction—strong interaction (nature domination)—strong interaction (human domination) model, validated in other regions of the world for long time scale human-nature interactions.